Debussy's Cakewalk. Race, Modernism and Music in Early Twentieth-Century Paris - Deaville, James (Revue musicale OICRM)

(untitled) (OICRM, 2014)
Between November, 1902 and January, 1903, Paris experienced its first tastes of the danced cakewalk through the performances of two American touring ensembles: “Les Elks” and their troupe of black and white dancers appeared in the revue Les joyeux nègres at the Nouveau Cirque, while the “Florida Creole Girls”—seven African-American women—performed the cakewalk at the Casino de Paris. Within a matter of weeks the dance became the latest sensation of the capital, as reported in Paris qui chante of January, 1903, although not without serious dissension. It was upon this field of social and cultural contestation that Debussy entered into the world of syncopated Americanism with Golliwogg’s Cake-Walk from the Children’s Corner (1908). This was followed by The Little Nigar (1909), the theme of which he reused in Le boîte à joujoux (1913); Minstrels from the first book of Préludes (1910), which more subtly draws upon cakewalk rhythms; and “General Lavine”-Eccentric from the second book (1910-1913), for which he uses the tempo designation “Dans le style et le mouvement d’un cake-walk.” While the literature about Debussy and fin-de-siècle music does reference this music and his indebtedness to the cakewalk and ragtime, it has largely failed to position him within the prevailing discourse surrounding the dance, which includes the film Le cake-walk infernal by Georges Méliès (1903). This paper proposes to explore the four aforementioned works by Debussy from the perspective of the contemporary debate over the cakewalk in French culture and society. Rather than attributing to the composer a particular subject position regarding blacks and their culture through his appropriation of the cakewalk, we will explore what it meant for Debussy to align himself with those elements of Parisian society that embraced the dance form and its music. However, as we shall see in the case of Debussy and his Parisian milieu, the modernist adoption of the cakewalk was fraught with problematic constructions of race, which cannot be ignored.